PENGEMBANGAN LKPD MENGGUNAKAN MODEL PJBL UNTUK MENUMBUHKAN KARAKTER RASA INGIN TAHU MATERI MAKNA PANCASILA SISWA KELAS IV SD - Nova Lucianti, Brigita; Purnomo, Puji (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is based on the importance of developing quality LKPD, and prioritizing student-centered learning in order to foster a character of curiosity that is in line with curriculum development. The purpose of this study is to develop LKPD using the project-based learning model on the meaning of Pancasila material for grade IV elementary school. The type of research used is Research and Development (R&D) type ADDIE. The data collection techniques used are interviews and questionnaires. This study uses qualitative and quantitative data analysis techniques. This study used 4 certified grade IV elementary school teacher validators who acted as expert judgment. In addition, 25 students participated in the product trial. The results of this study indicate that 1) The development of LKPD using the project-based learning model for the meaning of Pancasila material for grade IV elementary school was carried out using ADDIE steps including: Analyze, Design, Development, Implement, and Evaluate. 2) The quality of LKPD using the project-based learning model for the meaning of Pancasila material for grade IV elementary school obtained an average validation score of 3.79 with the category "very good". The results of limited trials show that LKPD is effective in developing students' curiosity character with a percentage increase of 70% with an N-Gain Score of 0.84 in the high category and LKPD improves learning outcomes with a level of effectiveness in the high category (N-Gain Score 0.82).